Public administration aspects of community development programmes - United Nations Technical Assistance Programme (New York : Office for Public Administration, United Nations, 1959)
This study analyses the public administration aspects of community development programmes, defines distinctive public administration problems involved in such programmes, and suggests research and other activities that may lead to a better understanding of these problems and to methods for their solution.
"ST/TAO/M/14".
At head of title: United Nations technical assistance programme.
Includes bibliographical footnotes.
ahz 04/04/2019
Loans
Keywords: Public administration; Community administration